Applying M-sequences Decimation to Generate Interleaved Sequence - Truong, Dang Van; Quynh, Le Chi (Journal of Science and Technology on Information security, 2022)
Abstract— M-sequences are widely used in for many purposes, from synchronization, whitening, communications and cryptography. We analyze decimation techniques and introduce two methods to generate decimation sequences which don’t have to calculate intermediate states. Then we apply these methods to interleaved sequence as a new method to pre-calculate for set of interleaved order which is more effective in implementation.